Inovasi digital public relations dalam mendukung transformasi digital perbankan syariah - Azkya, Vaizul (Maliki Interdisciplinary Journal, 2024)
This research discusses the importance of digital transformation through the implementation of Digital Public Relations (Digital PR) to build a positive image, enhance customer trust, and strengthen relationships with stakeholders. Using a qualitative approach, this research identifies the role of PR in managing online reputation, developing relevant publication strategies, and establishing effective communication with the audience. Challenges faced, such as data protection and technology misuse, must be addressed to achieve successful digital transformation. By leveraging social media and digital content, Islamic banks can reach a broader audience, improve operational efficiency, and remain competitive in the banking industry. This research demonstrates that PR not only serves to manage image but also contributes to the success of digital transformation in Islamic banking.